2014
DOI: 10.1038/cmi.2014.44
|View full text |Cite
|
Sign up to set email alerts
|

Ly49 receptors activate angiogenic mouse DBA+ uterine natural killer cells

Abstract: In humans, specific patterns of killer immunoglobulin-like receptors (KIRs) expressed by uterine natural killer (uNK) cells are linked through HLA-C with pregnancy complications (infertility, recurrent spontaneous abortion, intrauterine growth restriction and preeclampsia). To identify mechanisms underpinning the associations between NK cell activation and pregnancy success, pregnancies were studied in mice with genetic knockdown (KD) of the MHC-activated Ly49 receptor gene family. B6.Ly49 KD pregnancies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…Pregnant females with pan Ly49 downregulation had deficient decidual angiogenesis at gd6.5 and decreased VEGFA expression by DBA 1 uNK cells at gd9.5-10.5. 134 These data suggest that the reported human gestational complications linked to conceptus genotypes unable to activate uNK cells maybe based upon inadequate uNK cell-driven angiogenesis.…”
Section: Unk Cell Receptors That Regulate Angiogenesis In Decidua Basmentioning
confidence: 95%
See 2 more Smart Citations
“…Pregnant females with pan Ly49 downregulation had deficient decidual angiogenesis at gd6.5 and decreased VEGFA expression by DBA 1 uNK cells at gd9.5-10.5. 134 These data suggest that the reported human gestational complications linked to conceptus genotypes unable to activate uNK cells maybe based upon inadequate uNK cell-driven angiogenesis.…”
Section: Unk Cell Receptors That Regulate Angiogenesis In Decidua Basmentioning
confidence: 95%
“…44 Depletion or activation defects of DBA 1 uNK cells cause diminished VEGFA expression, reduced blood vessel density and reduced numbers of large sinuses. 26,88,132,133 In some of these mouse models, subfertility 134 and intrauterine growth restriction 26,133,134 are present. However, undefined compensatory mechanisms develop that successfully support these pregnancies to term.…”
Section: Pruning Of Vesselsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Influences on leukocyte recruitment as well as on trophoblast invasion are discussed in normal as well as in pathological pregnancies. Lima and her colleagues 14 then report on the roles of the LY49 receptor gene family during mouse pregnancy, focusing on subsets of uterine natural killer (NK) cells. These authors found selective alterations of NK cell functions in pan LY49 gene knockdown mice.…”
mentioning
confidence: 99%
“…[1][2][3] The dynamic changes in the uterine immune system induced over the course of a healthy pregnancy were also discussed. 2,[4][5][6][7] In Issue 2 of this special topic mini-series, the contributed papers are more clinically oriented and address current understanding of the immunological aspects of common pathologies that complicate human and livestock reproduction. Rodent models that provide key translational insights are blended with the clinical information.…”
mentioning
confidence: 99%